Cardiac magnetic resonance derived global longitudinal strain outperfoms established functional parameters in prognostication after ST-elevation myocardial infarction. (25th November 2020) - Holzknecht, M; Reindl, M; Tiller, C; Lechner, I; Hornung, T; Plappert, D; Klug, G; Reinstadler, S.J; Bauer, A; Mayr, A; Metzler, B
Abstract: Background: Left ventricular ejection fraction (LVEF) is the parameter of choice for left ventricular (LV) function assessment and risk stratification of patients with ST-elevation myocardial infarction (STEMI); however, its prognostic value is limited. Other measures of LV function such as global longitudinal strain (GLS) and mitral annular plane systolic excursion (MAPSE) might provide additional prognostic information post-STEMI. However, comprehensive investigations comparing these parameters in terms of prediction of hard clinical events following STEMI are lacking so far. Purpose: We aimed to investigate the comparative prognostic value of LVEF, MAPSE and GLS by cardiac magnetic resonance (CMR) imaging in the acute stage post-STEMI for the occurrence of major adverse cardiac events (MACE). Methods: This observational study included 407 consecutive acute STEMI patients treated with primary percutaneous coronary intervention (PCI). Comprehensive CMR investigations were performed 3 [interquartile range (IQR): 2–4] days after PCI to determine LVEF, GLS and MAPSE as well as myocardial infarct characteristics. Primary endpoint was the occurrence of MACE defined as composite of death, re-infarction and congestive heart failure. Results: During a follow-up of 21 [IQR: 12–50] months, 40 (10%) patients experienced MACE. LVEF (p=0.005), MAPSE (p=0.001) and GLS (p<0.001) were significantly related to MACE. GLS showed the highest prognostic value with an area under the curve (AUC) of 0.71 (95% CI 0.63–0.79; p<0.001) compared to MAPSE (AUC: 0.67, 95% CI 0.58–0.75; p=0.001) and LVEF (AUC: 0.64, 95% CI 0.54–0.73; p=0.005). After multivariable analysis, GLS emerged as sole independent predictor of MACE (HR: 1.22, 95% CI 1.11–1.35; p<0.001). Of note, GLS remained associated with MACE (p<0.001) even after adjustment for infarct size and microvascular obstruction. Conclusion: CMR-derived GLS emerged as strong and independent predictor of MACE after acute STEMI with additive prognostic validity to LVEF and parameters of myocardial damage. Funding Acknowledgement: Type of funding source: None